2000
DOI: 10.2214/ajr.174.2.1740367
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clinically Silent Intracranial Emboli Ipsilateral to Internal Carotid Occlusions During Cerebral Angiography

Abstract: Emboli seen in middle cerebral arteries ipsilateral to occluded ICAs during cerebral angiography strongly indicate that emboli can occur distal to an occlusion. Our findings support the thought that emboli arising from sources proximal to an occluded ICA may reach the hemisphere distal to the occlusion, resulting in parenchymal ischemia or infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…[6][7][8] Performance of arch aortography may lead to greater numbers of emboli thus leading to higher procedure complication rates than selective carotid angiography and is not infrequently performed by less welltrained practitioners. 8,21 All of the above-mentioned factors, including procedural time and multiple catheter use, are not independent and are typically related to inexperience and lack of specialized training in the cervicocerebral circulation. 8,12 The effect of training and experience, and/or lack thereof, was clearly shown in a 5000-angiogram analysis that demonstrated that fellowship-trained specialists have fewer neurological complications (0.5%) than even experienced angiographers (0.6%), and both have far fewer complications than trainees under supervision (2.8%).…”
Section: Risks Of Cervicocerebral Angiographic Procedures Risks Of Dmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Performance of arch aortography may lead to greater numbers of emboli thus leading to higher procedure complication rates than selective carotid angiography and is not infrequently performed by less welltrained practitioners. 8,21 All of the above-mentioned factors, including procedural time and multiple catheter use, are not independent and are typically related to inexperience and lack of specialized training in the cervicocerebral circulation. 8,12 The effect of training and experience, and/or lack thereof, was clearly shown in a 5000-angiogram analysis that demonstrated that fellowship-trained specialists have fewer neurological complications (0.5%) than even experienced angiographers (0.6%), and both have far fewer complications than trainees under supervision (2.8%).…”
Section: Risks Of Cervicocerebral Angiographic Procedures Risks Of Dmentioning
confidence: 99%
“…"Silent" neuropathological sequelae of cerebral embolism are even more common than overt, clinically demonstrable neurological complications. 20,21,[23][24][25] The fact that thromboembolic occurrences may be "silent", yet still represent serious pathologic brain damage has recently been described in two magnetic resonance imaging (MRI) studies where diffusion weighted pulse sequences ideal for detecting small infarcts were obtained after angiography. 23,24 In one study, small new areas of brain infarction without overt clinical correlates were identified in 25% of 66 patients after diagnostic cerebral angiography.…”
Section: Risks Of Cervicocerebral Angiographic Procedures Risks Of Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Operator risk factors for angiographically produced ischemic complications (temporary and/or permanent stroke) are well known and include increased procedure and fluoroscopy time, increased number of catheters used, and performance of arch aortography (6)(7)(8). Performance of arch aortography may lead to greater numbers of emboli, thus leading to higher procedure complication rates than selective carotid angiography and is not infrequently performed by less welltrained practitioners (8,21). All of the aforementioned factors, including procedural time and multiple catheter use, are not independent and are typically related to inexperience and lack of specialized training in the cervico-cerebral circulation (8,12).…”
Section: Risks Of Cervicocerebral Angiographic Procedures Diagnostic mentioning
confidence: 99%
“…"Silent" neuropathologic sequelae of cerebral embolism are even more common than overt, clinically demonstrable neurologic complications (20,21,(23)(24)(25). The fact that thromboembolic occurrences may be silent, yet still represent serious pathologic brain damage has recently been described in two magnetic resonance (MR) imaging studies in which diffusion-weighted pulse sequences ideal for detecting small infarcts were obtained after angiography (23,24).…”
Section: Risks Of Cervicocerebral Angiographic Procedures Diagnostic mentioning
confidence: 99%